Nanotechnology in cosmetics: the legal challenges in Malaysia/ Siti Hanum Mohmad Sah, Masturina Mohamad Rodzi and Puteri NorNadia Mohamed Iqbal - Mohmad Sah, Siti Hanum; Mohamad Rodzi, Masturina; Mohamed Iqbal, Puteri Nor Nadia (Faculty of Law, 2008)
This project paper on nanotechnology in cosmetic is written to observe the legal challenges arising from the development of the technology. The issue of nanotechnology arises due to the reason that despite the vast development of nanotechnology there is yet a complete research done on nanotechnology, on whether the technology is safe. Scientist worldwide has often expressed their concerns that nano-particles in cosmetic would have its own potential harm towards users. One of the major developments of nanotechnology is in the cosmetic industries where smaller particles work better. Our market search confirms that nano-cosmetic products are available on the market shelf despite the lacking in the legislation and research done. Our major research strategy is by a quantitative analysis and references are mainly obtained from the internet and scientific journals. Data have been collected from surveys conducted and published reports on nanotechnology in cosmetic and people's awareness on this matter. Response from the survey shows that 82% of respondents are unaware of any potential harm of nanocosmetic and the lack of law thereof. These situations confirm the low level of awareness among Malaysian on this issue and therefore boost the necessity for us to target on the legal challenges of nano-cosmetic.